Rhodanine-based Knoevenagel reaction and ring-opening polymerization for efficiently constructing multicyclic polymers - Zhang, Ze; Nie, Xuan; Wang, Fei; Chen, Guang; Huang, Wei-Qiang; Xia, Lei; Zhang, Wen-Jian; Hao, Zong-Yao; Hong, Chun-Yan; Wang, Long-Hai; You, Ye-Zi (Nature communications, 2020)
Cyclic polymers have a number of unique physical properties compared with those of their linear counterparts. However, the methods for the synthesis of cyclic polymers are very limited, and some multicyclic polymers are still not accessible now. Here, we found that the five˗membered cyclic structure and electron withdrawing groups make methylene in rhodanine highly active to aldehyde via highly efficient Knoevenagel reaction. Also, rhodanine can act as an initiator for anionic ring-opening polymerization of thiirane to produce cyclic polythioethers. Therefore, rhodanine can serve as both an initiator for ring-opening polymerization and a monomer in Knoevenagel polymerization. Via rhodanine-based Knoevenagel reaction, we can easily incorporate rhodanine moieties in the backbone, side chain, branched chain, etc, and correspondingly could produce cyclic structures in the backbone, side chain, branched chain, etc, via rhodanine˗based anionic ring-opening polymerization. This rhodanine chemistry would provide easy access to a wide variety of complex multicyclic polymers. Cyclic polymers have a number of unique physical properties compared to their linear counterparts but their synthesis is very limited. Here, the authors show a method to form a wide variety of multicyclic polymers by a rhodanine˗based Knoevenagel reaction and ring-opening polymerization.